PELAKSANAAN PEMBERIAN KREDIT DENGAN JAMINAN ANGGUNAN YANG TIDAK JADIKAN SEBAGAI HAK TANGGUNGAN PADA PERUMDA BPR ROKAN HULU - Rizki Hamdani; Almadison (Journal Of Juridische Analyse, 2023)
The term credit comes from the Latin "Credere" which means trust, it can be concluded that a credit grant can occur if it contains the trust of a person or entity that gives credit to those who receive credit (debtors/customers). While the Definition of Credit According to Banking Law No. 10 of 1998 Credit is the provision of money or bills, based on a loan agreement or agreement between a bank and another party that requires the borrower to pay off his debt after a certain period of time with interest. The 1937-190 Staatsblad was declared no longer valid. Article 1 point 1 of the UUHT, regulates the Mortgage Right on Land and Land-Related Objects, hereinafter referred to as the Mortgage Right, which is a guarantee right that is imposed on land rights as referred to in the UUPA, including or without other objects that is an integral part of the land, for the settlement of certain debts, which gives priority to certain creditors over other creditors. Whereas in the case of land rights that are used as collateral, they have not been certified before the registration of Mortgage Rights is carried out. The time of the seventh day determined as the book date of the Mortgage Land in such case, is calculated from the completion of the registration of the land rights in question